Poria Attenuates Idiosyncratic Liver Injury Induced by Polygoni Multiflori Radix Praeparata - Gao, Dan; Pang, Jing-Yao; Zhang, Cong-En; Li, Chun-Yu; Tu, Can; Zhang, Hai-Zhu; Niu, Ming; Xiong, Yin; Xiao, Xiao-He; Zhao, Kui-Jun; Gao, Wei-Wei; Wang, Jia-Bo (Frontiers in Pharmacology, 2016)
The hepatotoxicity induced by Polygoni Multiflori Radix Praeparata (PM) has aroused great concern throughout the world. Hence, it is worthwhile to perform studies on the detoxification with the combined use of medicinal herbs based on the compatibility theory of traditional Chinese medicine. In this work, the rat model of PM/LPS-induced idiosyncratic liver injury was used. The effects of Poria, Licorice, and Panax notoginseng on rats of PM/LPS-induced liver injury were investigated respectively, hoping to find the most effective herbal medicine to reduce the hepatotoxicity. According to results of biochemical and histological tests, PM could induce the idiosyncratic hepatotoxicity of rats which presented modest inflammation triggered by non-injurious dose of lipopolysaccharide (LPS). We also found that the combined use of Poria and PM in the ratio of 1:2 could significantly ameliorate the PM/LPS-induced liver injury and systemic inflammation. Furthermore, UPLC/QTOF-MS-based metabolomics was performed to identify possible biomarkers and underlying biological pathways. Ten metabolites were expressed differentially among LPS, PM/LPS, and detoxification-treated groups in terms of PCA and OPLS-DA analysis, which could be potential biomarkers. MetaboAnalyst and pathway enrichment analysis revealed that alterations of these metabolites were primarily involved in three pathways: arginine and proline metabolism, primary bile acid biosynthesis and sphingolipid metabolism. This research provides systematic experimental evidences for the hepatoprotective effect of Poria against PM/LPS-induced liver injury for the first time. And these findings may help better understand the underlying mechanisms of pathophysiologic changes in PM/LPS-induced liver injury.